The effect of using plyometric exercises by the method of intermittent training on the vertical jump and recovery ability of basketball players - بافة عبدالله; زمام عبدالرحمان (sports creativity, 2025)
The purpose of this study was to examine the effects of plyometric exercises using intermittent training on vertical jump and recovery ability of basketball players. The subjects included 08 players from CSK khemis Miliana. The researcher used the experimental approach and the training program was applied for a period of (06) Weeks and at a rate of (02) two sessions per week, after the process of data collection and statistical analysis, the researcher concluded that plyometric exercises using intermittent training positively affect the development of the vertical jump and recovery capacity of basketball players